2003
DOI: 10.1677/joe.0.1770319
|View full text |Cite
|
Sign up to set email alerts
|

Localization of estrogen receptors-alpha and -beta and androgen receptor in the human growth plate at different pubertal stages

Abstract: Sex steroids are required for a normal pubertal growth spurt and fusion of the human epiphyseal growth plate. However, the localization of sex steroid receptors in the human pubertal growth plate remains controversial. We have investigated the expression of estrogen receptor (ER) , ER and androgen receptor (AR) in biopsies of proximal tibial growth plates obtained during epiphyseal surgery in 16 boys and eight girls. All pubertal stages were represented (Tanner stages 1-5). ER , ER and AR were visualized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 46 publications
2
68
1
Order By: Relevance
“…Immunohistochemistry was performed as previously described (19) with the following modifications. After antigen retrieval by incubating with trypsin (Invitrogen) for 10 min at 37°C, the sections were additionally treated with 5 mg/mL hyaluronidase (Sigma Chemical Co.-Aldrich, Inc, Steinheim, Germany) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described (19) with the following modifications. After antigen retrieval by incubating with trypsin (Invitrogen) for 10 min at 37°C, the sections were additionally treated with 5 mg/mL hyaluronidase (Sigma Chemical Co.-Aldrich, Inc, Steinheim, Germany) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Some organs are capable of synthesising sex steroids from sulphated precursors which are present in high amounts in the circulation. The term 'intracrinology' was introduced, suggesting that sex steroids can be synthesised locally and act in the same cell without being released, indicating that a more complicated mechanism may be available in the physis [12,13,18,29].…”
Section: Endocrinology Of Growth and Pubertymentioning
confidence: 99%
“…(9) The two nuclear ERs, ERa and ERb, as well as the membrane Gprotein-coupled receptor GPR30 proposed to be an ER, are expressed in growth plate cartilage. (10)(11)(12)(13)(14)(15)(16) ERa is the main functional ER in the mouse growth plate, although ERb slightly modulates longitudinal bone growth in female but not in male mice. (17,18) We recently demonstrated that female GPR30 À/À mice displayed reduced longitudinal bone growth and reduced growth plate height that could not be reduced further by E2 treatment.…”
Section: J Jbmrmentioning
confidence: 99%